Understanding the Policy Context and Conditions Necessary for the Establishment of Supervised Consumption Sites in Canada - Chaviva Manson-Singer; Sara Allin (McMaster University Library Press, 2020)
The establishment of supervised consumption sites (SCS) is one policy approach used to address Canada's growing, national opioid epidemic. Despite the abundance of evidence which demonstrates the numerous public health benefits gained from the existence of SCS, only five of ten Canadian provinces have established SCS. Using Alberta and Manitoba as comparators, the paper seeks to explain the difference in policy outcomes. The paper begins with a brief overview of the history of harm reduction policy in Canada and establishes what the goals of the Alberta and Manitoba governments were in their respective policy approaches to respond to the opioid epidemic. Using John Kingdon's Multiple Streams Framework, this paper compares the political and policy contexts of Alberta and Manitoba to determine what factors have contributed to the divergence in policy outcomes, whereby Alberta has established SCS while Manitoba has not. The comparative analysis reveals that the framing of the opioid epidemic as a public health matter, the alignment of the establishment of SCS with the provincial government's values, and political will are all necessary conditions for the establishment of SCS. This paper concludes by discussing the implications of these results for the establishment of SCS in other Canadian provinces. Ouvrir des sites de consommation supervisée (SCS) est une approche utilisée pour affronter l'épidémie nationale croissante d'opioïdes au Canada. En dépit de l'abondance d'évidence démontrant les bénéfices pour la santé publique de ces SCS, seuls cinq des dix provinces canadiennes en ont établis. En utilisant l'Alberta et le Manitoba comme comparateurs, cet article cherche à expliquer les différences de politiques. L'article commence par présenter brièvement l'histoire de la politique de réduction des dommages au Canada et montre quels buts les gouvernements de l'Alberta et du Manitoba s'étaient assignés dans leurs approches politiques respectives pour répondre à l'épidémie des opioïdes. Suivant le schéma des courants multiples de John Kingdon, cet article compare les contextes politiques et les processus de prise de décision politique en Alberta et au Manitoba afin de déterminer quels facteurs ont contribué à la divergence des politiques mises en place, à savoir que l'Alberta a établi des SCS, mais pas le Manitoba. L'analyse comparative révèle que positionner l'épidémie d'opioïdes comme un problème de santé publique compte, et que l'alignement de la mise en place de SCS avec les valeurs du gouvernement provincial, ainsi que la volonté politique sont des conditions nécessaires pour la mise en place de SCS. Cet article conclue en discutant les conséquences de ces observations pour la mise en place de SCS dans les autres provinces canadiennes.